Genetic variability, heritability and correlation in chrysanthemum (Dendranthema grandiflora) - J, SHRAVANI; U, SREELATHA; BASHEER, SHAJMA NAFEESA; SANKAR, MINI; S, MINIMOL J (The Indian Journal of Agricultural Sciences, 2024)
Chrysanthemum is a herbaceous perennial flowering crop that holds great potential for commercial cultivation. Fifteen chrysanthemum genotypes were studied at the Department of Floriculture and Landscaping, College of Agriculture, Vellanikkara, Kerala Agricultural University, Thrissur, Kerala during 2022 for variability studies in morphological, flowering and post-harvest parameters. Significant variations were recorded among the genotypes for all the traits. Cluster analysis grouped the 15 chrysanthemum genotypes into 4 clusters based on all the characters. Cluster 2 consists of maximum number of 5 genotypes followed by 4 genotypes each in cluster 3 and cluster 4. Highest intra-cluster distance was recorded for cluster 2 and highest inter-cluster distance was observed between cluster 1 and 4. Results revealed that GCV was greater than the equivalent PCV, indicating that the environment had a negligible influence on phenotypic variation. High heritability coupled with high genetic advance for all the characters, indicating additive gene effect suggests that there is excellent scope for selection and improvement. Flower yield per plant showed a substantial positive correlation with flowers/plant, flower diameter, stalk length, stalk girth and flower weight at both phenotypic and genotypic level which could be focused for yield improvement.